Trade integration and business tax differentials: Evidence from OECD countries - Nelly Exbrayat; Benny Geys (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2012)
Building on recent contributions to the New Economic Geography literature, this paper analyses the relation between asymmetric market size, trade integration and business income tax differentials across countries. First, relying on Ottaviano and Van Ypersele's (2005) foot-loose capital model of tax competition, we illustrate that trade integration reduces the importance of relative market size for differences in the extent of corporate taxation between countries. Then, using a dataset of 26 OECD countries over the period 1982-2004, we provide supportive evidence of these theoretical predictions: i.e., market size differences are strongly positively correlated with corporate income tax differences across countries but, crucially, trade integration weakens this link. These findings are obtained controlling for the potential endogeneity of trade integration and are robust to alternative specifications.
Keywords: H2; H3; C23; F12; 330; tax competition; trade integration; new economic geography; tax differentials